Understanding Students’ Needs in an English Class through a Diagnostic Test - Mala Rovikasari; Desi Antri Astuti; Anida Fadhilah Jati (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Running effective teaching-learning activities can be a challenge for English teachers due to the lack of understanding students’ needs. Therefore, knowing the students’ strengths and weaknesses is important in English class. This research aims at investigating the students’ needs related to the English materials through a diagnostic test. The type of this research is descriptive qualitative research. The data were collected by using a test that had been taken by 20 students who were in the second semester of eight grade at a Junior High School in one of Indonesia’s small cities. The result shows the English materials which are needed to be focused on by the English teacher before starting the class for the ninth grade. The diagnostic test helps the English teacher to prepare the English materials that fit with the students’ needs. Keywords: diagnostic test, assessment, English learning materials